2017
DOI: 10.1177/002795011724200110
|View full text |Cite
|
Sign up to set email alerts
|

International Trade and UK De-Industrialisation

Abstract: The past 25 years have been characterised by a surge in international trade as economies have become increasingly inter-linked. In many advanced economies this surge has been associated with increased import competition from low-wage economies. This paper explores the effects of such competition on manufacturing jobs in the UK. We consider two developments that influenced the nature of international trade: the ascendency of China as an important player in global markets and the accession to the European Union … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 15 publications
3
28
0
Order By: Relevance
“…Reduced-form analyses of geographic regions have been used to study the labour market impacts of Chinese import competition in many developed economies, including the UK (Foliano and Riley, 2017), Germany (Dauth, Findeisen and Suedekum, 2014), France (Malgouyres, 2017a), Italy (Citino and Linarello, 2019), Spain , Norway (Balsvik, Jensen and Salvanes, 2015) and the US (Autor, Dorn and Hanson, 2013a). These studies produce three common findings.…”
Section: The Impact Of Import Competition On Firms and Workersmentioning
confidence: 99%
See 1 more Smart Citation
“…Reduced-form analyses of geographic regions have been used to study the labour market impacts of Chinese import competition in many developed economies, including the UK (Foliano and Riley, 2017), Germany (Dauth, Findeisen and Suedekum, 2014), France (Malgouyres, 2017a), Italy (Citino and Linarello, 2019), Spain , Norway (Balsvik, Jensen and Salvanes, 2015) and the US (Autor, Dorn and Hanson, 2013a). These studies produce three common findings.…”
Section: The Impact Of Import Competition On Firms and Workersmentioning
confidence: 99%
“…To investigate the reaction of a country's labour market to a trade shock of a given magnitude more systematically, we next study results from comparable local labour market analyses from the UK (Foliano and Riley, 2017), Germany (Dauth, Findeisen and Suedekum, 2014), Spain , Norway (Balsvik, Jensen and Salvanes, 2015) and the US (Autor, Dorn and Hanson, 2013a). A common feature of these studies is that they estimate the impact of Chinese import competition (measured in thousand dollars of imports per worker) on the share of a country's working-age population that is employed in manufacturing.…”
Section: International Comparison Of the China Shock's Labour Market ...mentioning
confidence: 99%
“…For further examples with more or less similar results, see Balsvik et al . () for Norway, Crozet and Orefice () for France, Foliano and Riley () for the United Kingdom and Nilsson Hakkala and Huttunen () for Finland.…”
Section: Research On Individual Drivers Of Inequalitymentioning
confidence: 99%
“…Between 2000 and 2007, the number of manufacturing jobs in the U.S. shrank by one‐fifth (3.6 million), while manufacturing employment in Britain fell by over one‐quarter, with a loss of almost a million jobs (Berger & Martin, :14; Rhodes, :7). Analysis suggested that China's export surge was responsible for one‐quarter of U.S. manufacturing job losses over the period 1990 to 2007, and from one‐fifth to one‐third of the decline in Britain between 2000 and 2015 (Autor et al, ; Foliano & Riley, :R11).…”
Section: Uneven and Combined Development: The Conjuncture Of 2016mentioning
confidence: 99%